The Analysis on the Use of Past Tense Found in the Students' Recount Writing - Khalawi, Hasan; Wibawa, Saptanto Hari (English Language Education, Universitas Internasional Batam, 2022)
Errors are common problems faced by foreign language learners during the learning process. The errors are affected by the mother tongue and other conditions. In this case, the problems occurred at the English department students at STKIP PGRI Pacitan. Therefore, the solution should be found by the lecturers by employing qualitative research-type error analysis to reveal the problems. The procedures of this research were: 1) preparation (formulating the research problem; 2) formulating the title, extensive literature survey, and preparing the research design; 3) determining sample design; 4) collecting the data, execution of the project); 5) processing (analysis of data, conclusion), report writing. Moreover, there were 40 students as the subject of this research. To get the data, the researcher took the answer sheets of essay writing of recount text to be analyzed qualitatively. In conformity with the findings, errors based on the use of past form are as the following: past simple 422 errors or 96%, past perfect 13 errors or 2,98%, past continues 1 error or 1% and past perfect continues 0 or 0%. It means that the frequent error made by the students was in using simple past tense and the absence of errors in using past perfect, past continuous, and past perfect continuous. Henceforth, the lecturers should provide more appropriate approaches and methods to solve the problematic errors.